Pengembangan Aplikasi Pembelajaran Interaktif Berbantuan Kodular untuk Meningkatkan Kemampuan Literasi Matematika Siswa Materi SPLDV - Lisa, Nur Khalisah; Ahmad Farham Majid; Alanuari; Shahriani S (Griya Journal of Mathematics Education and Application, 2025)
The development of technology-based interactive learning media is needed in the world of education, because it can help solve learning problems in the classroom, enrich the learning process, and increase students' creativity, motivation, and mathematical literacy skills. However, the availability of this interactive learning application is still very limited. Based on this, this research was conducted with the aim of developing Kodular-assisted interactive learning applications that are expected to improve the mathematical literacy skills of class VIII K students on SPLDV (System of Linear Equations of Two Variables) material. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Students of class VIII K at SMP Negeri 3 Sungguminasa were the subjects in this study. Data collection was conducted through observation, interviews, questionnaires, and learning outcomes tests. Data processing through analysis of validity, practicality and effectiveness. The results showed that the Kodular-based interactive learning application on SPLDV material has met the criteria of valid, practical, and effective. In addition, students' mathematical literacy skills have increased after the application of the application. Therefore, this interactive learning application can be used as a solution to improve students' mathematical literacy skills.